(3GYJdGd GdbdhHs - (3eMeO Hf LYaQ Hf eMeO Hf Sgd CHh HcQ GdNQGFWj GdSGeQj , CHh HcQ,J (B327 (3g` s ((3UNQI Hjf GdebOS s)
(3ChdgG (B:s
(3CNHQfG GdTjN CHh GdaVd GdZRfhi bGd (B:(3CNHQfG CHh HcQ eMeO Hf LYaQ Hf Sgd GdNQGFWi bGd GdMeO ddg GdMcje GdYdje s
(3BNQgG (B:s
(3aGSJGPf YdjgG hCfTOgG GdHjJjf ,Ke bGd (B:(3eG JCeQjf ? bGdJ BeQg HJbhi Gddg Je GdLRA GdKGef ef GYJdGd GdbdhH hgh BNQ GdcJGH s
(3QhGjI CHj GdYHGS CMeO Hf EHQGgje Hf Ydi GdcfOi Ys
(3di MhGTi GdfSNI HYV JUMjMGJ heWdYGJ ai GdbQfjf GdSGHY hGdKGef s
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs